2021
DOI: 10.1038/s41419-021-04122-8
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 protects dendrite cells against ferroptosis induced by sepsis

Abstract: Ferroptosis is a nonapoptotic form of programmed cell death triggered by the accumulation of reactive oxygen species (ROS) depended on iron overload. Although most investigations focus on the relationship between ferroptosis and cancer, neurodegenerative diseases, and ischemia/reperfusion injury, research on ferroptosis induced by immune-related inflammatory diseases, especially sepsis, is scarce. Sestrin2 (Sesn2), a highly evolutionary and stress-responsive protein, is critically involved in defense against o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…In the late stage of sepsis, macrophages will release high mobility group protein B1 (HMGB1), which can stimulate the expression of Sesn2 in DCs ( 82 ). Sesn2 inhibits the ferroptosis of DCs in sepsis by down-regulating the ATF4-CHOP-CHAC1 signaling pathway and exerts an antioxidant effect ( 83 ). This discovery inspires us that exploring the relationship between sepsis and ferroptosis may help us overcome sepsis, a disease that seriously threatens human health.…”
Section: Immune Cells and Ferroptosismentioning
confidence: 99%
“…In the late stage of sepsis, macrophages will release high mobility group protein B1 (HMGB1), which can stimulate the expression of Sesn2 in DCs ( 82 ). Sesn2 inhibits the ferroptosis of DCs in sepsis by down-regulating the ATF4-CHOP-CHAC1 signaling pathway and exerts an antioxidant effect ( 83 ). This discovery inspires us that exploring the relationship between sepsis and ferroptosis may help us overcome sepsis, a disease that seriously threatens human health.…”
Section: Immune Cells and Ferroptosismentioning
confidence: 99%
“…Ferroptosis is iron-dependent and characterized by the accumulation of intracellular ROS and lipid peroxidation products (Dixon et al, 2012;Li et al, 2021). To explore the influences of LPS and VitB6 on non-heme iron, we measured iron levels in serum and myocardial tissue.…”
Section: Vitb6 Alleviates Lps-induced Non-heme Iron Increasementioning
confidence: 99%
“…Ferroptosis comprehends a new cell death type, distinct from apoptosis, necrosis, and autophagy in genetical, biochemical, and morphological aspects (Dixon et al, 2012). This iron-dependent cell death type is characterized by the accumulation of intracellular reactive oxygen species (ROS) and lipid peroxidation products (Dixon et al, 2012;Li et al, 2021). Many researchers demonstrated that ferroptosis can be related to multiple diseases, such as ischemia-reperfusion (I/R)-induced cardiomyopathy (Fang et al, 2019), kidney degeneration, neurodegenerative diseases (Stockwell et al, 2017), and various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis was firstly identified by Dolma et al (7) in cancer cells and was found to be different from apoptosis, pyroptosis, and necroptosis, which are also involved in neurotoxicity, kidney injury, liver injury, and heart disease (8)(9)(10). Due to its role in multiple organs, ferroptosis has also been implicated in sepsis (11). However, the genetic background of ferroptosis in sepsis remains elusive.…”
Section: Introductionmentioning
confidence: 99%